RETRACTED ARTICLE: An extension of the fuzzy improved risk graph and fuzzy analytical hierarchy process for determination of chemical complex safety integrity levels. Issue 4 (2nd October 2019) - Yazdi, Mohammad
Abstract : We, the Editors and Publisher of International Journal of Occupational Safety and Ergonomics, have retracted the following article: Mohammad Yazdi. An extension of the fuzzy improved risk graph and fuzzy analytical hierarchy process for determination of chemical complex safety integrity levels . International Journal of Occupational Safety and Ergonomics . 2019; 25 (4): 551-561. doi:10.1080/10803548.2017.1419654 The above article has been retracted as a result of an article with a significant overlap in content having been published in Persian in the Journal of Health and Safety at Work as Qorbali Z, et al . Representing the Fuzzy improved risk graph for determination of optimized safety integrity level in industrial setting. JHSW. 2013; 3 (3); 79-90. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".